2020
DOI: 10.3390/brainsci10060325
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychological Profile of Attention Deficits of Patients with Obstructive Sleep Apnea: An Update on the Daytime Attentional Impairment

Abstract: Introduction: Patients with obstructive sleep apnea (OSA) suffer from several neurocognitive disturbances. One of the neuropsychological processes most investigated in OSA patients is attention, but the results have been controversial. Here, we update the attention profile of OSA patients with the final aim to improve attention assessment, with a possible impact on clinical and medical-legal practices, in terms of which attention subdomains and parameters need consideration and which one is a high-risk OSA phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 86 publications
3
17
0
Order By: Relevance
“…This result may be justified as; the increase in Apnea Hypopnea Index with aging may be related to the increase in weight and the total number of respiratory arousals was significantly decreased in the elderly with OSA. The result of this study is in agreement with a study done in Japan by Hongyo et al, (2016) 19 and in Brazil by Zhao, Viana, Ma & Capasso, (2018) 20 who found that the severity of OSA in elderly patients increased with aging.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result may be justified as; the increase in Apnea Hypopnea Index with aging may be related to the increase in weight and the total number of respiratory arousals was significantly decreased in the elderly with OSA. The result of this study is in agreement with a study done in Japan by Hongyo et al, (2016) 19 and in Brazil by Zhao, Viana, Ma & Capasso, (2018) 20 who found that the severity of OSA in elderly patients increased with aging.…”
Section: Discussionsupporting
confidence: 93%
“…This result may be justified as; EDS is a common complaint in patients with OSA. This result agrees with a study done in Turkey by Balcan & Ozsancak Ugurlu, (2017) 16 and In Italy by Angelelli et al, (2020) 17 who found that most of the studied elders were sleepy. In contrast, a study was done in France by Sforza, Pichot, Martin, Barthelemy & Roche, (2016) 18 reported that only 15% of the patients had excessive daytime sleepiness.…”
Section: Discussionsupporting
confidence: 92%
“…Also, frequent awakenings, episodes of oxyhemoglobin desaturation, and fluctuations of heart-rate, systemic and pulmonary artery pressure are observed. Affected individuals generally report to suffering from excessive daytime sleepiness, sleep fragmentation, and drowsiness, together with decreased energy, reduced level of concentration and alertness, and overall cognitive difficulties (i.e., Akashiba et al, 2002;Zhou et al, 2016;Simões et al, 2018;Angelelli et al, 2020). Crucially, these symptoms impact negatively on individuals' efficacy in daily-life activities, such as working, driving, social interaction, and they increase the risk of (work-or road-) accidents (Vaessen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial volume of evidence has linked pediatric OSA and cardiovascular/metabolic dysfunctions [ 1 , 2 ]. Some research has also suggested a connection between pediatric OSA and neurocognitive/behavioral impairment, but the results are still inconsistent and inconclusive [ 3 ]. Adenotonsillectomy remains the preferred treatment for pediatric OSA [ 4 , 5 ]; however, older children have been reported to have less satisfactory surgical outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%